Market structure and cartel duration: Evidence from detected EU cartel cases - Sandra Maria Swoboda (Westfälische Wilhelms-Universität Münster, Institut für Genossenschaftswesen (IfG), 2018)
Cartel duration is influenced by market structure but it also varies depending on the cause of cartel death. This paper distinguishes between determinants which increase the probability of death by leniency application and those that increase the probability of death through intervention by competition authorities. Proportional hazard models with competing risks are applied to detected EU cartel cases for the period 2001 to 2017. The analysis indicates that the existence of industry specific problems or high cumulative market share do not give cartel members an incentive to apply for leniency, whereas companies which benefit from advantages or the existence of buyer power on the demand side are more likely to denounce the cartel. Regardless of the cause of their death, cartels lasted longer if they operated across different markets. Likewise, the probability of cartel detection by competition authorities decreases if cartel agreements affect heterogeneous products. In contrast, detection probability increases if companies are organised around an industry association with regular meetings or in case the cartel has a leader. – – Die Kartelldauer kann je nach Ursache des Kartellzusammenbruchs variieren. Dieses Arbeitspapier unterscheidet zwischen den Ursachen der Inanspruchnahme der Kronzeugenregelung und der selbstständigen Ermittlungen von Wettbewerbsbehörden. Es werden Proportional Hazard Modelle für bereits aufgedeckte EU-Kartellfälle im Zeitraum von 2001 bis 2017 geschätzt. Die Analyse zeigt, dass die Existenz von Problemen in einer Branche oder ein hoher kumulativer Marktanteil dazu führen, dass Kartelle später durch die Kronzeugenregelung aufgedeckt werden. Im Gegensatz dazu führen Vorteile in einer Branche oder Käufermacht dazu, dass Unternehmen ihr eigenes Kartell eher bei den Wettbewerbsbehörden anzeigen. Unabhängig von der Ursache des Kartellzusammenbruchs ist ein Kartell von längerer Dauer, wenn die Unternehmen auf mehreren Märkten tätig sind. Die Wahrscheinlichkeit einer Kartellaufdeckung durch Wettbewerbsbehörden sinkt, wenn heterogene Produkte Gegenstand der Absprachen sind. Im Gegensatz dazu steigt diese Wahrscheinlichkeit, wenn die Unternehmen an Verbandstreffen teilnehmen oder ein Kartellführer existiert.
Keywords: 330